Rejuvenating the past: the significance of adaptive reuse for historical buildings in Kayutangan, Malang, Indonesia - Anthea Putri Yasmin; Herry Santosa; Jenny Ernawati (Cogent Arts & Humanities, 2025)
Malang, a city with various architectural heritage from the Dutch colonial era, is being branded as a Heritage City by the city mayor. One of Malang’s historic areas, Kayutangan, was developed into the city’s heritage capital to implement the city’s image, including the Kayutangan Street Corridor (KSC). During its development, inactive historic buildings come back to life because the building replaces or adds new functions. The combination of the development of the KSC into a new city public space and the return to life of inactive buildings have made this area alive with people. Therefore, this study investigates the influence of a building’s new design concept on adaptively reused buildings in the KSC area. This study used a mean score test, factor analysis, and multiple linear regression to determine the public’s preference for the suitability of adaptively reused building design with its function and increasing activities. Architects and stakeholders can consider the results of this study when redesigning historic buildings to maintain their authenticity. The governments can also consider the findings of this study to make policies for planning historic city areas to preserve the visual authenticity of the area related to the existing buildings to strengthen the area’s character.